Evaluation of Antidiabetic Potential of Eucalyptus Globulus Plant Extract In Alloxan-Induced Diabetic Rats - Kamble, Ujwala B.; Chaware, V. J; Redasani, V. K. (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: Evaluation of Antidiabetic Potential of Eucalyptus globules Plant Extract in Alloxan- Induced Diabetic Rats. Method: Methanolic leaves extract of Eucalyptus globulus plant was prepared by Soxhlet extraction method and stored in refrigerator at 4℃ for two days before use. Male Albino Wistar rats were made diabetic at the dose of Alloxan (150mg/kg/day i.p.). Methanolic leaves extract of Eucalyptus globulus plant (200mg/kg, 400mg/kg & 600mg/kg/day p.o.) was screened for antidiabetic activity. Standard drug Glibenclamide (0.5mg/kg/day i.p.) was administered to the second group of animals for 14 days. Blood glucose level and body weight of rats were recorded on Initial & Final days of treatment. Further hypoglycemic & OGTT evaluation were done. At the end of treatment biochemical estimations & histopathological examination of pancreas were also carried out. Result: The statistical data indicated, 14 Days oral administration of Methanolic leaves extract of Eucalyptus globulus plant caused a significant (????< 0.05) reductions in blood glucose level, hypoglycemicpotential, significant oral glucose tolerance &gain in body weight as compared with toxic control group. Further showed improvement in altered biochemical parameters associated with diabetes. Concurrent histopathological examination of pancreas of these animals showed regeneration by Methanolic leaves extract which were earlier necrosed by Alloxan. Conclusion: Results obtained in this study substantiate the Antidiabetic potential of Methanolic leaves extract of Eucalyptus globulus plant the source of Ellagitannins a bioactive polyphenol and could be considered for further evaluation in clinical studies and drug development.